ANTI-VIRAL EFFECTS OF MEDICINAL PLANTS IN THE MANAGEMENT OF DENGUE: A SYSTEMATIC REVIEW - Frederico, Éric Heleno Freira Ferreira; Dionísio Cardoso, André Luiz Bandeira; Moreira- Marconi, Eloá; de Sá-Caputo, Danúbia da Cunha; Sampaio Guimarães, Carlos Alberto; Fontoura Dionello, Carla da; Morel, Danielle Soares; Paineiras-Domingos, Laisa Liane; de Souza, Patricia Lopes; Brandão-Sobrinho-Neto, Samuel; Carvalho-Lima, Rafaelle Pacheco; Guedes-Aguiar, Eliane de Oliveira; et al. (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Dengue is considered as an important arboviral disease. Safe, low-cost, and effective drugs that possessinhibitory activity against dengue virus (DENV) are mostly needed to try to combat the dengue infection worldwide.Medicinal plants have been considered as an important alternative to manage several diseases, such as dengue. Asauthors have demonstrated the antiviral effect of medicinal plants against DENV, the aim of this study was to reviewsystematically the published research concerning the use of medicinal plants in the management of dengue using thePubMed database.Materials and Methods: Search and selection of publications were made using the PubMed database following theguidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA statement).Results: Six publications met the inclusion criteria and were included in the final selection after thorough analysis.Conclusion: It is suggested that medicinal plants’ products could be used as potential anti-DENV agents.